Pragmatic Functions of Perlocutionary Act in F-3 Leveled Reading Book - Musriyono, Anna Ardiyani; Rustono, Rustono; Saptono, Sigit (Journal of Primary Education, 2018)
Perlocutionary act is a speech act spoken by a speaker to influence the interlocutors and can be found in the communication process. One form of communication process can be found in conversations between the characters in story from children's reading books. Perlocutionary act is uttered with different pragmatic functions according to the context of the speech. The objectives of this research are (1) to describe the functions of perlocutionary act in F-3 leveled reading book, and (2) to determine the dominant perlocutionary act function in F-3 leveled reading book. The research approach used in this research was pragmatic approach and qualitative descriptive approach. The data collection was conducted by using observation method with recording technique. After the data have been analyzed using heuristic method, the result of the research shows that (1) 12 perlocutionary acts are found in F-3 leveled reading book with five kinds of functions, which are the function of relieving, persuading, convincing, attention-grabbing, and scaring and (2) the most dominant perlocutionary act function in F-3 leveled reading book is relieving function with total seven speeches. This research is expected to give contributions to the academic study, especially in the field of pragmatic study.